A Study on the Relationship between Proprietorship Concentration and Profit Management in the Companies Listed in Tehran Stock Exchange - Ranjbarian, Soghra; Rezaei, Akbar Zavari; Azizi, Asghar (Journal of History Culture and Art Research, 2017)
The presence of institutional investors may change the behaviors of companies. The impact of institutional investors on management decisions on financial affairs have been proven in other studies; yet, the present study aims to investigate the relationship between lack of information symmetry an concentration of proprietorship with profit management in the companies listed in Tehran Stock Exchange. The period under study included years 2004 to 2009. Rahavard Novin Computer application was utilized to collect the data; then they were calculated using Microsoft Excel. SPSS computer application was used to test research hypothesis and conduct other statistical analysis using statistical methods like descriptive statistics, correlation (correlation coefficient, coefficient of determination), regression analysis and testing its coefficients, correlation analysis and test of coefficients and significance of the difference between two correlation coefficients. A total of 109 active companies in the stock exchange were selected as the sample of the study. Results on the first hypothesis revealed that the relationship between concentration of proprietorship and lack of information symmetry. In case of the second hypothesis, it is predicted that there is a significant relationship between profit management with lack of information symmetry and concentration of proprietorship. According to research results, investors and analysts ought to pay attention to factors like proprietorship composition, the level of information symmetry along with the figures published by the companies when making short and long-term decisions.